Isolasi Bakteri Inti Es pada Kentang - Triwidodo Arwiyanto (Universitas Gadjah Mada, 1996)
Frost injury is one of the limiting factors in potato production in Dieng (2000 m above sea level), Central Java. The damage caused by frost has been recorded since long time ago, however, there is no studies about this matter. The objective of the present study is to isolate ice nucleation active bacteria which reside epiphytically at the surface of potato leaves. Potato and several crop leaves were collected and the ice catalyst was detected from leaf-washing. The bacteria were isolated on Nutrien Agar and Nutrien Agar Glycerol medium. The result indicated that ice catalyst was detected from the leaf washing of potato (Solanum tuberosum L.) and broad bean (Vicia faba L.) but not from others. The ice catalyst was not detected from the extract of surface soil, neither. The ice nucleation active bacteria were successfully isolated from potato leaf and were identical to Erwinia ananas in their bacteriological properties.